ChemInform Abstract: Novel Layered Perovskite Sr3Ti2O7:Eu3+ Phosphor with High‐Efficiency Luminescence Enhanced by Charge Compensation. Issue 6 (21st January 2016) - Zhang, Le; Sun, Bingheng; Liu, Quan; Ding, Nan; Yang, Hao; Wang, Lixi; Zhang, Qitu
Abstract: The Sr3 Ti2 O7 :Eu 3+ (5%) red phosphor with double‐layered perovskite structure is prepared by ball milling (8 h) of SrCO3, TiO2, and Eu2 O3 prior to calcination in air (1000—1300 °C, 2 h).